2017
DOI: 10.4103/ijdr.ijdr_771_16
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells in dentistry: A study regarding awareness of stem cells among dental professionals

Abstract: This study revealed a good level of awareness among the dental professionals, and it also showed the need to spread more knowledge about the advances in applications, storage, banking, and guidelines related to dental stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This is similar to the previous study, suggesting the need to review the current curriculum and include new technologies and methods in learning and practicing [20]. The higher cost of regenerative treatment and stem cells was the biggest obstacle to patients accepting such treatment, as reported by 61.7% of participants, higher than the findings reported by Chitroda et al [26] and Epelman et al [23]. The higher cost of such treatment might be due to the more expensive types of equipment and the hard work needed.…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to the previous study, suggesting the need to review the current curriculum and include new technologies and methods in learning and practicing [20]. The higher cost of regenerative treatment and stem cells was the biggest obstacle to patients accepting such treatment, as reported by 61.7% of participants, higher than the findings reported by Chitroda et al [26] and Epelman et al [23]. The higher cost of such treatment might be due to the more expensive types of equipment and the hard work needed.…”
Section: Discussionsupporting
confidence: 88%
“…A similar study was conducted for other populations in India regarding awareness of stem cells and showed that dental professionals had a good level of awareness, but it also highlighted the need for more information to be shared about the developments in DSC applications, storage, banking, and guidelines. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Nigeria also reported that the majority (60.3%) of the dentists had poor knowledge of stem cells' potential in regenerative dentistry 23 . Whereas, in India, only 53.9% of dental professionals found to have awareness about the regenerative potential of stem cells from the dental origin 24 . In contrast, about 81.5% of Malaysian medical students were aware of umbilical cord stem cells compared to stem cells from other sources 25 .…”
Section: Discussionmentioning
confidence: 99%